2015
DOI: 10.1002/jid.3147
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Remittances on Children's Human Capital Accumulation: Evidence from Morocco

Abstract: Using a nationally representative household data set from Morocco, the present study seeks to estimate the effects of migrants' remittances on household investments in children's human capital. Three findings emerge. First, children in remittance-receiving households are more likely to attend school and less likely to drop out compared with those in non-remittance-receiving households. Second, children's participation in labour market decreases in the presence of international remittances. Third, remittances a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…In the same line, a study by Adams (1998), which focused on Egypt and Pakistani, found that remittances receiving households spent much of these foreign cash flows on land and housing besides they have a higher marginal propensity to save compared to nonreceiving households. From a different perspective, Acharya and Leon-Gonzalez (2018), Azam and Raza (2016) and Bouoiyour and Miftah (2016) contend that households may opt to spend foreign remittances on human capital and related opportunity with a greater potential for future income. Several studies have linked foreign remittances to higher school retention rates (Pilařová & Kandakov, 2017;Kumar, 2019;Edward & Ureta, 2003).…”
Section: Foreign Remittances and Private Sector Investmentmentioning
confidence: 99%
“…In the same line, a study by Adams (1998), which focused on Egypt and Pakistani, found that remittances receiving households spent much of these foreign cash flows on land and housing besides they have a higher marginal propensity to save compared to nonreceiving households. From a different perspective, Acharya and Leon-Gonzalez (2018), Azam and Raza (2016) and Bouoiyour and Miftah (2016) contend that households may opt to spend foreign remittances on human capital and related opportunity with a greater potential for future income. Several studies have linked foreign remittances to higher school retention rates (Pilařová & Kandakov, 2017;Kumar, 2019;Edward & Ureta, 2003).…”
Section: Foreign Remittances and Private Sector Investmentmentioning
confidence: 99%
“…Characteristics of children and their caregivers may also influence whether and how frequently remittances are received, although Nobles () found no evidence that the age and gender of nonmigrant children in Mexico influenced the financial contributions of migrant fathers. Others have emphasised that gender bias may be more evident in the allocation of remittances (Antman, ; Bouoiyour & Miftah, ). In some contexts, a bias in favour of girls and younger boys has been found in the spending of remittances on education (Acosta, ) and health care (Lopez‐Ekra, Aghazarm, Kötter, & Mollard, ), whereas other studies have found the opposite effect, with a bias in favour of boys (Hu, ; Lu & Treiman, ).…”
Section: Transnational Parenting and Children's Time Use: Conceptualimentioning
confidence: 99%
“…Estudios tan antiguos como el Adams (1989) determinaron que la migración internacional tiende a empeorar la desigualdad económica; y estudios más recientes como Bouoiyour & Miftah (2014) sugieren que las entradas de remesas aumentan la desigualdad de ingresos. Recientes trabajos empíricos sugieren que la migración y las remesas pueden aumentar o disminuir la desigualdad de la distribución del ingreso familiar.…”
Section: Coeficiente De Gini En El Ecuador 1990-2018unclassified